PEMETAAN ASET DAN POTENSI EKONOMI LOKAL MASYARAKAT DUSUN P. NAULI : STRATEGI PEMBERDAYAAN MELALUI PROGRAM KKN BERBASIS ASSET BASED COMMUNITY DEVELOPMENT (ABCD) - Efendi, Rahmad; Siregar, Rahmat Mubarok; Haqq, Wadinil; Siregar, Jahara; Hasibuan, Husnaini (STIE Mahardhika, 2025)
This study aims to map the assets and local economic potential of the community in Pardomuan Nauli Hamlet, Selayang Baru Village, Selesai Subdistrict, Langkat Regency, by employing the Asset-Based Community Development (ABCD) approach. Pardomuan Nauli Hamlet possesses unique characteristics, as the majority of its residents are of Batak ethnicity, maintaining strong customary traditions, and are religiously homogeneous (Christian and Catholic). The research employed a descriptive qualitative method, with data collected through in-depth interviews, participatory observation, and documentation. The primary informant in this study was the Head of Pardomuan Nauli Hamlet. The findings reveal that the community possesses six major categories of assets: natural assets, consisting of 65 hectares of productive rice fields, rubber, and oil palm plantations; human assets, with a predominance of people within the productive age range (20–50 years) and aspirations for higher education; social assets, represented by the Serikat Tolong Menolong (STM), which plays a central role in customary and social solidarity; cultural assets, reflected in the preservation of Batak traditions in marriage, death rituals, and genealogical systems; religious assets, encompassing nine churches that serve as both spiritual and social centers; and physical assets, such as water pumps and rice threshing machines. Nevertheless, the community also faces several challenges, including dependence on rice farming that is vulnerable to crop failure due to pests, the high cost of fertilizers and pesticides, the limited involvement of youth in social organizations, and insufficient healthcare facilities and road infrastructure. Based on these findings, relevant empowerment strategies include mobilizing local assets through the establishment of farmer cooperatives grounded in STM and church networks, diversifying agricultural products, strengthening the role of youth, and promoting Batak traditions as a potential cultural tourism attraction. Thus, the application of the ABCD approach in Pardomuan Nauli Hamlet can strengthen economic self-reliance while simultaneously preserving the community’s cultural identity.